2014
DOI: 10.1039/c4cp01355g
|View full text |Cite
|
Sign up to set email alerts
|

Chemically-bound xenon in fibrous silica

Abstract: High-level quantum chemical calculations reported here predict the existence and remarkable stability, of chemically-bound xenon atoms in fibrous silica. The results may support the suggestion of Sanloup and coworkers that chemically-bound xenon and silica account for the problem of ''missing xenon'' (by a factor of 20!) from the atmospheres of Earth and Mars. So far, the host silica was assumed to be quartz, which is in contradiction with theory. The xenon-fibrous silica molecule is computed to be stable well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Xe is surrounded by four O atoms in a quasi‐planar configuration, for both Xe Si(1h) and Xe Si(4u) , with Xe‐O bond lengths equal to 2.02–2.09 Å, that is, close to the sum of covalent radii of Xe and O (~2 Å). This result is similar to predicted mechanism of Xe incorporation in fibrous silica, where Xe substituted for Si with a planar local environment formed by four oxygen atoms and Xe‐O bond lengths of 2.17 Å (Kalinowski et al, ). However, this result differs from Xe incorporation in olivine: although Xe also substituted for Si with a quasi‐planar local environment and Xe‐O bonds lengths circa 2 Å, Xe was surrounded only by three O atoms in olivine (Crépisson et al, ).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Xe is surrounded by four O atoms in a quasi‐planar configuration, for both Xe Si(1h) and Xe Si(4u) , with Xe‐O bond lengths equal to 2.02–2.09 Å, that is, close to the sum of covalent radii of Xe and O (~2 Å). This result is similar to predicted mechanism of Xe incorporation in fibrous silica, where Xe substituted for Si with a planar local environment formed by four oxygen atoms and Xe‐O bond lengths of 2.17 Å (Kalinowski et al, ). However, this result differs from Xe incorporation in olivine: although Xe also substituted for Si with a quasi‐planar local environment and Xe‐O bonds lengths circa 2 Å, Xe was surrounded only by three O atoms in olivine (Crépisson et al, ).…”
Section: Resultssupporting
confidence: 88%
“…Probert () investigated Xe for Si and Xe for O substitutions, as well as Xe at interstitial site in α‐quartz by ab initio calculation using the density functional theory (DFT). All Xe incorporation mechanisms are stable at 0 and 2 GPa (i.e., the two investigated P ), although there is an energy barrier at T = 0 K. Xe incorporation in fibrous silica, studied theoretically using post Hartree‐Fock methods (Kalinowski et al, ), also occurs through substitution to Si surrounded by four oxygen atoms in fibrous silica, forming a stable compound well above room T .…”
Section: Introductionmentioning
confidence: 99%
“…Probert (2010) investigated different incorporation 113 mechanisms of Xe in α-quartz, but the lack of related measurements prevents definitive 114 conclusion. Kalinowski et al (2014) investigated Xe incorporation in fibrous silica, which can 115 be found on Earth in moganite or chalcedoine (Hopkinson et al, 1999). Computed Raman 116 spectra of Xe-bearing fibrous silica possibly reproduce observations for Xe-rich quartz 117 (Sanloup et al, 2002) and XeO 2 (Brock and Schrobilgen, 2011).…”
mentioning
confidence: 81%
“…Figure 3) that appear under P upon heating above the melting curve of Xe, the reaction being thermodynamically favored by the volume reduction between reactants (i.e., liquid Xe and quartz or olivine) and products (i.e., Xe-doped quartz or Xe-doped olivine). Theoretical calculations have confirmed this mechanism for quartz [43,76,77] and olivine [42], and helped refine the crystal-chemistry of Xe in these minerals. Volume and cell-parameters vs. P relationships as well as Raman signature of Xe-doped silicates could be theoretically reproduced by substituting Xe to Si albeit in different geometries depending on the mineral: quasi-planar three-fold in olivine vs. linear twofold (2 nearest O atoms at 1.99 Å) with 2 next nearest O neighbors in orthogonal plan at 2.27 Å in quartz [43].…”
Section: Xenon As a Minor/trace Element In Oxidesmentioning
confidence: 85%